Kidney failure risk equation (KFRE), a risk-based triage for nephrology referrals: a mixed-methods study at pre-implementation phase among healthcare providers - Rozi, Nur Raziana; Selvaraj, Christine Shamala; Tan, Jia Kai; Lim, Zhan Foong; Nordin, Noor Wahidah; Mazhar, Nuqman Hakimi; Hafizal, Haris; Beh, Hooi Chin; Lim, Quan Hziung; Ooi, Ying Guat; Abdullah, Adina; Wan Md Adnan, Wan Ahmad Hafiz; et al. (Elsevier, 2025)
Background: Chronic kidney disease (CKD) poses a significant health challenge globally. There is limited understanding of the challenges and opportunities to enhance CKD management from the perspectives of healthcare providers (HCPs) involved in the direct care of patients with CKD. To integrate a risk-based triage for nephrology referrals, namely the kidney failure risk equation (KFRE), we explored HCPs’ perspectives on the facilitators and barriers to CKD management before the implementation of KFRE.